Molecular genetic analysis of 30 families with Joubert syndrome. Issue 6 (26th September 2016) - Suzuki, T.; Miyake, N.; Tsurusaki, Y.; Okamoto, N.; Alkindy, A.; Inaba, A.; Sato, M.; Ito, S.; Muramatsu, K.; Kimura, S.; Ieda, D.; Saitoh, S.; et al.
Abstract : Joubert syndrome (JS) is rare recessive disorders characterized by the combination of hypoplasia/aplasia of the cerebellar vermis, thickened and elongated superior cerebellar peduncles, and a deep interpeduncular fossa which is defined by neuroimaging and is termed the 'molar tooth sign'. JS is genetically highly heterogeneous, with at least 29 disease genes being involved. To further understand the genetic causes of JS, we performed whole‐exome sequencing in 24 newly recruited JS families. Together with six previously reported families, we identified causative mutations in 25 out of 30 (24 + 6) families (83.3%). We identified eight mutated genes in 27 (21 + 6) Japanese families, TMEM67 (7/27, 25.9%) and CEP290 (6/27, 22.2%) were the most commonly mutated. Interestingly, 9 of 12 CEP290 disease alleles were c.6012‐12T>A (75.0%), an allele that has not been reported in non‐Japanese populations. Therefore c.6012‐12T>A is a common allele in the Japanese population. Importantly, one Japanese and one Omani families carried compound biallelic mutations in two distinct genes ( TMEM67 / RPGRIP1L and TMEM138 / BBS1, respectively). BBS1 is the causative gene in Bardet–Biedl syndrome. These concomitant mutations led to severe and/or complex clinical features in the patients, suggesting combined effects of different mutant genes. Abstract :